Perancangan Model Sistem Penelusuran Dwelling Time Terminal Peti Kemas Makassar PT. Pelabuhan Indonesia IV (PERSERO) - Fadli, Andi Muhammad; Syarif, Adi Chandra (TEMATIKA, Journal of Informatics and Information Systems, 2017)
This research are focused on designing systems that can perform data collection and the search report container.PT Pelabuhan Indonesa IV (Persero) Container Terminal Unit is a service company that is engaged in loading and unloading activities include stevedoring,Â cargodoring, and receiving / delivery.One of the causes of his old dwelling time at PT Pelabuhan Indonesa IV (Persero) Unit Container Terminal is inaccurate planning laying containers. This research uses a method of designing Rapid Application Development (RAD).Â Result of the research is a model system that can provide transparent information on the placement of the container in order to tracking the dwelling time.Keywords: container, dwelling time, PT Pelabuhan Indonesa IV (Persero), RAD, TPM.